Legal Protection for Buyers in The Sale and Purchase of Land With a Binding Sale and Purchase Agreement Based on a Notary's Power To Sell - Fasco Siregar, Hendrik; Nurwullan, Siti (Institute for Research and Community Service (LPPM), Universitas Dharma Indonesia (UNDHI), 2026)
Legal protection for good-faith land buyers is an important aspect in providing legal certainty and supporting the use and ownership of land in Indonesia. Buying and selling land as a legal product of high social and economic value is prone to default, such as non-submission of certificates, non-processing of the Sale and Purchase Deed, sale to other parties, or abuse of selling power. This study examines the form of legal protection for buyers, both preventive and repressive, and analyzes its effectiveness based on Article 1320 and Article 1243 of the Civil Code and Law Number 5 of 1960 concerning Agrarian Matters. Preventive efforts are carried out through agreements in accordance with the provisions of the law, while repressive efforts are taken through civil, criminal, and alternative dispute resolution channels. The results of the study show that the effectiveness of legal protection is greatly influenced by law enforcement, buyer awareness, and the role of the government and law enforcement officials in creating legal certainty in land purchase and sale transactions.